Wandering Towards a Goal How Can Mindless Mathematical Laws Give Rise to Aims and Intention? (The Frontiers Collection,, 2018)
This collection of prize-winning essays addresses the controversial question of how meaning and goals can emerge in a physical world governed by mathematical laws. What are the prerequisites for a system to have goals? What makes a physical process into a signal? Does eliminating the homunculus solve the problem? The three winning essays, by Larissa Albantakis, Carlo Rovelli and Jochen Szangolies tackle exactly these challenges, while many other aspects (agency, the role of the observer, causality versus teleology, ghosts in the machine etc.) put in an appearance in the other award winning contributions. These seventeen imaginative, stimulating and often entertaining essays are enhanced versions of the prize-winning entries to the FQXi essay competition in 2017. The Foundational Questions Institute, FQXi, catalyzes, supports, and disseminates research on questions at the foundations of physics and cosmology, particularly new frontiers and innovative ideas integral to a deep understanding of reality, but unlikely to be supported by conventional funding sources.